Borderline ovarian tumours in a middle-income country setting: a ten-year retrospective review of cases in a tertiary hospital in South Africa - Ghunney, Ama (Department of Obstetrics and Gynaecology, 2025)
The diagnosis and management of borderline ovarian tumours remain controversial almost a century after their initial description, and little research has been done in Africa to provide answers on the prevalence and outcomes of these tumours. This study is a review of cases of borderline ovarian tumours seen in Groote Schuur Hospital over a ten-year period. Objective: To describe the demographic characteristics, occurrence, treatment, and outcomes of women diagnosed with borderline ovarian tumour at Groote Schuur Hospital, a tertiary hospital in South Africa. Methods: A retrospective review of women diagnosed with borderline ovarian tumour in Groote Schuur Hospital between January 2005 and December 2014 was undertaken by reviewing our gynaecological oncology database and patients' folders. Women with multiple primary tumours, lost to follow-up, or with inadequate clinical data were excluded. Demographic characteristics, preoperative, operative, postoperative, oncologic, and pathologic data was retrieved and analyzed. Results: Ninety-one patients were diagnosed with borderline ovarian tumour in the study period. Nineteen were eliminated and 72 analysed. Borderline ovarian tumours accounted for 22.3% of 409 ovarian neoplasms registered with our gynaecological oncology database in the study period. The median age was 48.5 years, (range, 16–82 years) with 31.9% (n=23) of women less than 40 years of age. Seventy-point eight percent (n=51) of patients were completely surgically staged and 80.6% (n=58) were optimally debulked. Thirty-one-point nine percent (n=23) underwent fertility-sparing surgery and of these 17.4% (n=4) had completion surgery. Mucinous histology was the most common histological subtype (57%). The median time to recurrence was 42.9 months (range 1.0 to 108.0 months). Serous histology and fertility-sparing surgery were independently associated with recurrence (p=0.016, p=0.026 respectively). Our overall recurrence rate was 13.9% (n=10) with 40% of these being invasive (n=4). The 5-year overall survival rate was 91.7% and the 5-year relapse- free survival rate was 89.9%. Despite small numbers, all patients with invasive recurrence died within 5 years of recurrence, whiles all patients who recurred with borderline histology were alive 5 years after recurrence. Conclusion: Mucinous histology was the most common histological subtype (57%). Regardless of a generally favourable prognosis, patients who recurred as invasive disease were all dead 5 years after recurrence, whiles patients who recurred with borderline histology were all alive 5 years after recurrence.